Diagnostics of the Track Substructure Model and Its Practical Use - Libor Izvolt; Jan Kardos; Jan Lelak; Martin Mecar (Communications - Scientific letters of the University of Zilina, 2005)
The paper presents mathematical equations of dependence of deformation resistance (compaction degree) and static/dynamic deformation module of elasticity reached by experimental measurements at laboratory model of scale 1:1 in 2003 and 2004. Recommendations for practice from the point of view of dimensioning and suitability of applied materials into the railway substructure are also presented.